2015
DOI: 10.1007/s11067-015-9311-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Single Allocation Hub Location Problems

Abstract: Hubs are special facilities that serve as switching, transshipment and sorting nodes in many-to-many distribution systems. Flow is consolidated at hubs to exploit economies of scale and to reduce transportation costs between hubs. In this article, we first identify general features of optimal hub locations for single allocation hub location problems based on only the fundamental problem data (demand for travel and spatial locations). We then exploit this knowledge to develop a straightforward heuristic methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Reference [32] proposed a novel method for analyzing hub location problems by considering clustering-based potential hub sets. They define the travel demand of node as ( + ).…”
Section: Clustering-based Methodmentioning
confidence: 99%
See 3 more Smart Citations
“…Reference [32] proposed a novel method for analyzing hub location problems by considering clustering-based potential hub sets. They define the travel demand of node as ( + ).…”
Section: Clustering-based Methodmentioning
confidence: 99%
“…To generate the potential hub sets, all nodes need to be sorted by their importance, since the node importance depends on spatial properties and travel demands. The node importance can be measured with different formulations, and one of the best measures identified by [32] is as follows:…”
Section: Clustering-based Methodmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results showed that the GVNS based heuristics outperformed the bestknown heuristics in terms of solution quality and computational effort. Peker et al (2016) identified general features of optimal hub locations for the USApHMP and then exploited this knowledge to develop a straightforward heuristic methodology for solving the problem. Taner and Kara (2016) proposed a new approach to forecast the change in the demand patterns generated at different locations as a result of the placement of new hubs in the USApHMP.…”
Section: Literature Reviewmentioning
confidence: 99%